PENGARUH KEPUASAN KERJA DAN BUDAYA ORGANISASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN DI HORISON APARTEMEN DAN KONDOTEL YOGYAKARTA - Sudanang, Ertanta Ari; Priyanto, Sabda Elisa (Kepariwisataan: Jurnal Ilmiah, 2020)
The purpose of this study are: (1) Determine and analyze the effect of job satisfaction on employee productivity Horison Apartemen and Condotel Yogyakarta, (2) analyzing the effect cultural influence organization against employee productivity, (3) Know and analyze the influence of job satisfaction, and organizational culture on employee, and (4) Knowing and analyzing the variable job satisfaction and culture organization if there is a dominant effect on employee productivity. Type of research used in this research is the explanation. The variable in this study are job satisfaction, organizational culture, and work productivity. The populations in this study are all permanent employee of Horison Apartemen and Condotel Yogyakarta as many as 90 employees. Sampling in this study using the technique of total census or a questionnaire. The analysis tools are simple linear regression and multiple linear regretions. Based on these results it can be concluded that: (1) There is a positive and significant relationship between job satisfaction on employee productivity, (2) There is a positive and significant relationship between organizational culture on employee productivity, (3) There is a positive and significant relationship between job satisfaction and organizational culture on employee productivity in Horison Apartemen and Condotel Yogyakarta, and (4) There is a positive and significant relationship job satisfaction and organizational culture on employee productivity in Horison Apartemen and Condotel Yogyakarta. The higher variable is job satisfaction. (5) Variable job satisfaction is the most dominant variable influence on employees productivity in Horison Apartemen and Condotel Yogyakarta. Keywords: job satisfaction, organizational culture, work productivity